Battling Over Bathwater: Greywater Technopolitics in Los Angeles. (15th November 2021) - Randle, Sayd
Abstract: In Los Angeles, domestic wastewater recycling ("greywater") systems are controversial, loved by local environmentalists and disdained by the city's water agencies. Drawing on fieldwork among greywater advocates and public water agency workers, this article examines how greywater systems function as nodes that unsettle relations between residents and the public agencies that manage the city's water grid. Elaborating the longstanding frictions over greywater reuse in LA reveals how these fixtures are mobilized by advocates to rescript the roles of both individuals and the state within the urban waterscape. Detailing public agency workers' resistance to this form of selective disconnection from the grid helps to clarify the patterns of flows, norms of consumption, and forms of state control at stake in efforts to decentralize arrangements of urban water management.